2020
DOI: 10.1186/s41256-020-00167-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of air pollution on the incidence and mortality of COVID-19

Abstract: Air pollution is the most significant environmental risk factor for all-cause mortality, and it has caused substantial disability-adjusted life-years and economic loss. Air pollution intensified the mortality during past pandemics, Spanish flu in 1918 and SARS-CoV-1 in 2003. It increases host susceptibility and virulence of respiratory infections and reduces viral clearance. Thus, a question arises whether there will be any impact of air pollution on the current pandemic coronavirus disease 2019 (COVID-19)? Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
0
21
0
2
Order By: Relevance
“…Air pollution is the most significant environmental risk factor for all-cause mortality [ 8 ]. Increasing number of human epidemiologic studies has been conducted to assess the potential association between air pollution exposure and stroke admission, incidence, and mortality in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is the most significant environmental risk factor for all-cause mortality [ 8 ]. Increasing number of human epidemiologic studies has been conducted to assess the potential association between air pollution exposure and stroke admission, incidence, and mortality in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The risk was confirmed by epidemiologic data which indicate the increased COVID-19 mortality in the regions of Italy, Spain and England with the highest concentration of air pollutants [91]. The correlation between high levels of air pollution and increased numbers of COVID-19 cases has been noted also in France, the Czech Republic, and Poland [24].…”
Section: Disinfection and Sterilization During Covid-19mentioning
confidence: 67%
“…Reduction of community air pollution. Karan et al [91] indicated that the pollution of community air, mostly with PM 2.5 (particulate matter, described also as 'dust', with diameter less than 2.5 ÎĽm), NO 2 and SO 2 , may enhance the severity of COVID-19 by depression of the immunity, increasing host susceptibility to the infection and producing a significant pro-inflammatory state. According to Comunian et al [92], exposure to polluting agents alters the immune response of the lung cells and induces an increase in oxidative and inflammatory stress.…”
Section: Disinfection and Sterilization During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollutants increase host susceptibility to viral respiratory infections by increasing epithelial cells permeability to viral receptors and reducing host defense, thus impairing macrophage function and phagocytosis, antigen processing, and the expression of natural killer and cytotoxic T-cells. Pollutants may also increase the virulence of COVID-19 [86].…”
Section: Role Of Air Pollution In Spread and Severity Of Covid-19mentioning
confidence: 99%